Dynamic Testing & Simulation of 4 KW (5.5 Hp) Switched Reluctance Motor using PSpice - Rajesh Murlidharrao Autee (International Journal of Power Electronics and Drive Systems (IJPEDS), 2011)
In this paper, the requirement of mechanical model of SR Motor for determination of dynamic characteristic is presented. The PSpice is circuit oriented software package and it is believed that no direct mechanical models are available. Therefore electrical equivalent of mechanical sub systems were used for determination of dynamic characteristics.The variable inductor model is also proposed using voltage controlled component.Index Terms – Switched Reluctance Motor, Dynamic Characteristics, TorqueDOI: http://dx.doi.org/10.11591/ijpeds.v1i1.42